2018
DOI: 10.1111/psyp.13195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reward context on feedback processing as indexed by time‐frequency analysis

Abstract: The role of reward context has been investigated as an important factor in feedback processing. Previous work has demonstrated that the amplitude of the feedback negativity (FN) depends on the value of the outcome relative to the range of possible outcomes in a given context, not the objective value of the outcome. However, some research has shown that the FN does not scale with loss magnitude in loss-only contexts, suggesting that some contexts do not show a pattern of context dependence. Methodologically, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Delta‐RewP activity did not differentiate between outcome valence until the new sequence was established (i.e., the second trial of the same outcome). While our general finding that gains generated more Delta‐RewP aligns with previous reports from our group as well as others (Bernat et al., 2008, 2011, 2015; Bowers et al., 2018; Cohen et al., 2007; Ellis et al., 2018; Nelson et al., 2011; Watts et al., 2017; Watts & Bernat, 2018), the finding of a non‐significant difference in Delta‐RewP activity between gain and loss outcomes during the change trial is worth special consideration. Delta‐RewP has consistently been shown to be larger for gains relative to losses, but these prior studies would not have suggested such a lack of gain‐loss differences on the change trial.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Delta‐RewP activity did not differentiate between outcome valence until the new sequence was established (i.e., the second trial of the same outcome). While our general finding that gains generated more Delta‐RewP aligns with previous reports from our group as well as others (Bernat et al., 2008, 2011, 2015; Bowers et al., 2018; Cohen et al., 2007; Ellis et al., 2018; Nelson et al., 2011; Watts et al., 2017; Watts & Bernat, 2018), the finding of a non‐significant difference in Delta‐RewP activity between gain and loss outcomes during the change trial is worth special consideration. Delta‐RewP has consistently been shown to be larger for gains relative to losses, but these prior studies would not have suggested such a lack of gain‐loss differences on the change trial.…”
Section: Discussionsupporting
confidence: 93%
“…Theta is modulated by primary or the most salient stimulus characteristics (typically the gain/loss feedback), while delta is sensitive to both primary attributes as well as more complex secondary characteristics, such as relative outcome, outcome magnitude, and outcome expectancy (Bernat et al., 2015; Watts et al., 2017). Theta and delta have also shown differential sensitivity to loss and reward contexts (Watts & Bernat, 2018). Further, delta and theta have shown differential sensitivity to some aspects of psychopathology (Bernat et al., 2011; Foti et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, previous evidence suggests that the theta component of the reward response may be primarily sensitive to the most basic aspects of reward-related feedback, such as outcome, and may be insensitive to higher-order characteristics, such as experimental context (Bernat et al, 2015; Watts, Bachman, & Bernat, 2017; Watts & Bernat, 2018). Conversely, delta activity has been shown to be sensitive to higher-order attributes of reward-related feedback, such as context, magnitude, and expectancy (Bernat et al, 2015; Watts & Bernat, 2018; Watts et al, 2017), which suggests that delta activity may reflect elaborative processing of feedback stimuli. The present data, therefore, suggest that acute psychosocial stress did not impair basic performance monitoring; rather, it impaired the elaborative processing, and possibly reduced the motivational salience, of both positive and negative feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, previous evidence suggests that the theta component of the reward response may be primarily sensitive to the most basic aspects of reward-related feedback, such as outcome, and may be insensitive to higher-order characteristics, such as experimental context (Bernat et al, 2015;Watts, Bachman, & Bernat, 2017;Watts & ACUTE STRESS AND REWARD 25 Bernat, 2018). Conversely, delta activity has been shown to be sensitive to higher-order attributes of reward-related feedback, such as context, magnitude, and expectancy (Bernat et al, 2015;Watts et al, 2017;Watts & Bernat, 2018), suggesting that delta activity may reflect elaborative processing of feedback stimuli. The present data, therefore, suggest that acute psychosocial stress did not impair basic performance monitoring, but rather it impaired the elaborative processing, and possibly reduced the motivational salience, of both positive and negative feedback.…”
Section: Discussionmentioning
confidence: 99%